PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPETENSI APARATUR PEMERINTAH DAN KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI (Studi Empiris OPD Kota Pekanbaru) - Lestari Fitra; Sari Nelly Ria; Safitri Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study is to investigage the influance of transformational leadership style, government apparatus competence and clarity of budget targets on the performance accountability of government agencies with internal control as a moderating variable (empirical study on OPD in Pekanbaru city). The population in this study were all regional apparatus organizations of Pekanbaru City. The sample in this study amounted to 43 OPD with 129 respondents.The sampling method used in this study was saturated sampling technique, while the data processing method used in this study was the analysis of structural equation modeling (SEM) using the WarpPLS version 6.0 software.The results of study show that (1) transformational leadership style affects performance accountability with a significant value of 0.043 (<0.05). (2) the competence of government officials has a significant effect on agency performance with a significant value of 0.021 (<0.05). (3) Clarity of budget affects the accountability of agency performance with a significant value of 0.034 (<0.05). (4) control can strengthen the relationship of transformational leadership style to performance accountability with a significant value of 0.040 (<0.05). (5) Internal control strengthens the relationship between apparatus competence and performance accountability with a significant value of 0.001 (<0.05). (6) Internal control strengthens the relationship between the clarity of budget targets on performance accountability with a significant value of 0.001 (<0.05).Keyword : Leadership Style, Competence, Clarity Of Budget Objectives, Accountability, Internal Control